(untitled) (International Journal of Engineering and Computer Science, 2025)
The article analyzes the security threats of web applications and company websites. Two-tier and three-tier architectures of web applications are considered. An algorithm for assessing risks and searching for vulnerabilities in the web application infrastructure is presented, and the possibility of automating the testing process is noted. The most common threats to the security of web applications are identified. The main means of ensuring the security of web resources are provided.